THE PIVOTAL ROLE OF NOTARIES/PPAT IN THE PROTECTION OF PROTECTED RICE FIELD LAND - Diko Anggalih Utomo; Rahayu Subekti; Rosita Candrakirana (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The conversion of agricultural land is not a new issue. It is caused by population growth and economic development, which require infrastructure development in the form of roads, industrial buildings, and settlements that require land availability. The conversion of agricultural land is natural, but it can become a problem because it can reduce the amount of productive agricultural land. The purpose of this study is to analyze the effects of the Law on the Conversion of Protected Rice Fields into Non-Agricultural Land for Settlement or Housing and the role of Notaries/PPATs in relation to Protected Rice Fields in the Conversion of Land for Settlement or Housing. This study uses a normative juridical method. Legal materials are obtained through literature review. The analysis technique used is descriptive qualitative. The results of the study show that the conversion of protected rice fields to non-agricultural use that does not comply with regulations can have various legal consequences, ranging from administrative sanctions to criminal sanctions. Law enforcement in the conversion of protected rice fields needs to be carried out against perpetrators and officials who abuse their authority. Notaries/PPATs play an important role in preventing the conversion of rice fields to ensure that the authentic deeds made do not violate the law or regulations regarding protected rice fields.